2015
DOI: 10.3390/molecules200815158
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Variation Reveals a Sharp Genetic Break within the Distribution of the Blue Land Crab Cardisoma guanhumi in the Western Central Atlantic

Abstract: Abstract:The blue land crab Cardisoma guanhumi is widely distributed throughout tropical and subtropical estuarine regions in the Western Central Atlantic (WCA). Patterns of population genetic structure and historical demographics of the species were assessed by mtDNA control region sequence analysis to examine the connectivity among five populations (n = 97) within the region for future conservation strategies and decision-making of fishery management. A total of 234 polymorphic nucleotides were revealed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…It was reported that AMOVA could generate estimates of variance components, representing a correlation of haplotype diversities at different levels of hierarchical subdivision [ 36 ]. To some extent, AMOVA could further detect the existing factors that might have made sense for the formation of mtDNA diversity [ 23 , 37 ]. Therefore, we performed AMOVA by classifying 100 worldwide populations into various groups according to linguistic dialects and geographical regions ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that AMOVA could generate estimates of variance components, representing a correlation of haplotype diversities at different levels of hierarchical subdivision [ 36 ]. To some extent, AMOVA could further detect the existing factors that might have made sense for the formation of mtDNA diversity [ 23 , 37 ]. Therefore, we performed AMOVA by classifying 100 worldwide populations into various groups according to linguistic dialects and geographical regions ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Deoxyribonucleic acid (DNA) analysis on Leucocytozoon has been conducted to cytochrome b ( cyt b ) gene [ 8 ]. Series of genetic information in the mitochondrial DNA was reported to be able to portray the characteristics of a population and phylogenetics and able to reconstruct the evolutionary history [ 9 , 10 ]. cyt b gene is one of the genes located in the mitochondrial genome that is widely used for molecular analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with those of other crabs, the nucleotide diversity in the mtDNA CR of the P. pelagicus in the Gulf of Thailand was low. For example, the nucleotide diversity of the P. trituberculatus was 0.020 (Guo et al 2011) and 0.025 (Hui et al 2019), C. guanhumi was 0.027 (Amaral et al 2015), and E. mederi was 0.023 (Supmee et al 2012b). A high value of haplotype diversity but a low level of nucleotide diversity was presented within the P. pelagicus population in the Gulf of Thailand.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…The mutation rate in the mtDNA CR is approximately 5-10 times higher than other regions in the mitochondrial genome and is approximately 25-100 times higher than nuclear genes (Boore, 1999). It has been used to examine population genetic structure in various marine crabs such as Episesarma versicolor (Supmee et al 2012a), P. trituberculatus (Shan et al 2018), and Cardisoma guanhumi (Amaral et al 2015). Thus, mtDNA CR is one good DNA marker for studies of population structure.…”
Section: Introductionmentioning
confidence: 99%